Examining Monetary Policy Cyclicality in Egypt during Crisis Time: Global Financial Crisis versus COVID-19 Pandemic - Emam, Hebatalla Atef (International Journal of Economics and Financial Issues, 2024)
Egypt has been exposed to two recent shocks: the global financial crisis of 2008 and the COVID-19 Pandemic of 2020. Though the origin and the implications of the two shocks are quite different, they bear some similarities in terms of the sharp decline in global economic growth and negative implication on the Egyptian economy. The present study attempts to assess the cyclicality of monetary policy in Egypt during the two crises. To this end, both descriptive and econometric techniques are employed in this study to reveal the cyclicality of monetary policy. On the descriptive side, the correlation between the cyclical component of policy rate and that of real GDP is calculated. Moreover, both an ARDL and NARDL approach are estimated to derive the augmented Taylor rule for the cyclical component of policy rate. Two dummy variables reflecting the two crises along with their interaction with output gap are incorporated in the model to disentangle the impact of the two crises upon monetary policy cyclicality. The study concludes that monetary policy in Egypt is more acyclical and that its response to changes in output gap is statistically insignificant, during both normal times and crisis time.